MODAL SOSIAL: PEMBERDAYAAN MASYARAKAT DI PASAR MUSTOKOWENI DALAM MENGEMBANGKAN UMKM DI YOGYAKARTA - RISAL, SYAHLAN; Naufal, Muhammad; Ulhaq, M. Jia (Politeknik Kesejahteraan Sosial Bandung, 2024)
Mustokoweni Market is a weekly market in the city of Yogyakarta. This market can survive after Covid-19, where several other similar markets stop permanently, even with little finance. Therefore, this study aims to find out how this market can survive through the perspective of social capital and see how it is managed, by using the qualitative method of case studies, pattern matchmaking analysis. Data is collected through interviews, observations, documentation, and archival records. Validity is tested by triangulation of sources, theories, and methods. The results of this study show that in the management of the Mustokoweni Market, the leaders adopt an autocratic leadership style, this can be seen in leaders who handle all managerial affairs alone. As for the social capital that appears in the Mustokoweni Market, the norms of transparency, cognitive networks, ability trust patterns, less visible reciprocity, and proactive attitudes appear in market leaders. Keywords: Market, MSME Development, Social capital.